2020
DOI: 10.1111/acps.13233
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of bipolar disorder among young adults – a 22‐year community birth cohort

Abstract: Objective We set forth to build a prediction model of individuals who would develop bipolar disorder (BD) using machine learning techniques in a large birth cohort. Methods A total of 3748 subjects were studied at birth, 11, 15, 18, and 22 years of age in a community birth cohort. We used the elastic net algorithm with 10‐fold cross‐validation to predict which individuals would develop BD at endpoint (22 years) at each follow‐up visit before diagnosis (from birth up to 18 years). Afterward, we used the best mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…Prior studies have largely focused on individuals with a history of depression and/or have included relatively small samples. 27,28 Here, we All rights reserved. No reuse allowed without permission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have largely focused on individuals with a history of depression and/or have included relatively small samples. 27,28 Here, we All rights reserved. No reuse allowed without permission.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have largely focused on individuals with a history of depression and/or have included relatively small samples. 27,28 Here, we validated multiple algorithmic approaches across multiple well-powered longitudinal EHR sites in the absence of a common data model to generate a novel suite of prediction algorithms for BD. These models performed well across diverse geography and broad, heterogeneous patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…First, nine studies explicitly excluded participants with bipolar disorders, thus reducing the number of comparisons that could be made between unipolar and bipolar disorders in our synthesis. Difficulties in accurately diagnosing bipolar disorders, particularly in young people, are also an important factor (Rabelo-da-Ponte et al, 2020). Bipolar disorders are frequently misdiagnosed as MDD and other unipolar depressive conditions (Bowden, 2001; Phillips and Kupfer, 2013; Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, this study found that motor coordination, IPS, VL, and WM as predictors can accurately identify patients and first-degree relatives from the healthy population. This result can be applied to screening high-risk groups of bipolar disorder, so as to identify and intervene early (Rabelo-da-Ponte et al, 2020), prevent disease occurrence and improve disease prognosis (Correll et al, 2020).…”
Section: Discussionmentioning
confidence: 99%